KUALITAS AIR DAN STATUS KESUBURAN PERAIRAN DI TELAGA NGIPIK, WADUK BUNDER DAN TELAGA DOWO DI KABUPATEN GRESIK - Aminin Aminin; Gawes Bagus; Andrean Fajar Kusuma (Universitas Muhammadiyah Gresik, 2019)
Ngipik, bunder and dowo reservoirs or dowo are one of the repositories in Gresik regency located in the center of the city that has been utilized by the community for industrial, agricultural and domestic purposes, while also being used for tourism purposes. The study aims to determine water quality and evaluate the status of water fertility in three reservoirs/lakes (Ngipik, Bunder and Dowo) in Gresik district. The research activities were carried out from 16 to 20 July 2019. The data collection method used a survey method with stratified random sampling at three different stations. The results of water quality measurements show that overall that the water quality in the three reservoirs/ponds is still good for aquaculture activities except Ngipik Lake based on phosphate values of 0.75 - 3 ppm can be categorize including the status of dense eutrophic waters so specific management plans are needed to optimize its utilization. Whereas in the Bunder reservoir and Dowo ponds, the phosphate content has not detected, so its water status is oligotrophic.